The Microbiome and Maternal Newborn Health. Issue 6 (November 2017) - N/A,
Abstract : Dr. Irene Yang, guest editor of the special topic series on the pregnancy, mother, and baby microbiomes, discusses the clinical implications of the microbiome during childbirth and how maternal newborn nurse researchers at Emory University's Nell Hodgson Woodruff School of Nursing are at the forefront of investigating various aspects of this important new area of research.